Impact of peritoneal carcinomatosis on clinical outcomes of patients receiving self-expandable metal stents for malignant colorectal obstruction - Park, Jae Jun; Rhee, Kwangwon; Yoon, Jin Young; Park, Soo Jung; Kim, Joo Hee; Kim, Jie-Hyun; Youn, Young Hoon; Kim, Tae Il; Park, Hyojin; Kim, Won Ho; Cheon, Jae Hee (Endoscopy, 2018)
Background Peritoneal carcinomatosis can influence clinical outcomes of patients receiving self-expandable metal stents (SEMS) for malignant colorectal obstruction, but data regarding this issue are sparse. We analyzed the clinical outcomes of post-SEMS insertion for malignant colorectal obstruction based on carcinomatosis status.Methods Stent- and patient-related clinical outcomes were compared for carcinomatosis status in a retrospective review involving 323 consecutive patients (colorectal cancer 198 patients; extracolonic malignancy 125 patients) who underwent palliative SEMS placement for malignant colorectal obstruction from January 2005 to March 2012. Severity of carcinomatosis was classified as mild, moderate, or severe. Results Carcinomatosis was observed in 190 patients (58.8 %). The rates of technical (84.7 vs. 94.7 %; P = 0.005) and clinical (73.2 vs. 83.5 %; P = 0.03) success were lower in patients with vs. without carcinomatosis. Rates of early (2.1 % vs. 3.0 %; P = 0.72) and delayed (1.6 % vs. 6.0 %; P = 0.08) perforation and stent failure (27.9 % vs. 26.3 %; P = 0.75) showed no difference. Technical and clinical success rates were significantly different based on the severity of carcinomatosis (technical success rate: mild 90.7 %, moderate 97.4 %, severe 76.3 %, P = 0.003; clinical success rate: mild 83.3 %, moderate 82.1 %, severe 63.9 %, P = 0.01). In multivariate analysis, severe carcinomatosis was identified as an independent factor related to technical (odds ratio [OR] 0.18, 95 % confidence interval [CI] 0.06 – 0.56) and clinical (OR 0.33, 95 %CI 0.15 – 0.74) success.Conclusions Peritoneal carcinomatosis was associated with decreased technical and clinical success rates in patients receiving SEMS for malignant colorectal obstruction. Moreover, the presence of severe carcinomatosis was an independent factor determining these clinical outcomes.